Reducing VEGF-B Signaling Ameliorates Renal Lipotoxicity and Protects against Diabetic Kidney Disease - Falkevall, Annelie; Mehlem, Annika; Palombo, Isolde; Heller Sahlgren, Benjamin; Ebarasi, Lwaki; He, Liqun; Ytterberg, A. Jimmy; Olauson, Hannes; Axelsson, Jonas; Sundelin, Birgitta; Patrakka, Jaakko; Scotney, Pierre; et al. (Cell metabolism, 2017)
Diabetic kidney disease (DKD) is the most common cause of severe renal disease, and few treatment options are available today that prevent the progressive loss of renal function. DKD is characterized by altered glomerular filtration and proteinuria. A common observation in DKD is the presence of renal steatosis, but the mechanism(s) underlying this observation and to what extent they contribute to disease progression are unknown. Vascular endothelial growth factor B (VEGF-B) controls muscle lipid accumulation through regulation of endothelial fatty acid transport. Here, we demonstrate in experimental mouse models of DKD that renal VEGF-B expression correlates with the severity of disease. Inhibiting VEGF-B signaling in DKD mouse models reduces renal lipotoxicity, re-sensitizes podocytes to insulin signaling, inhibits the development of DKD-associated pathologies, and prevents renal dysfunction. Further, we show that elevated VEGF-B levels are found in patients with DKD, suggesting that VEGF-B antagonism represents a novel approach to treat DKD. [Display omitted] •Targeting VEGF-B signaling to reduce renal lipotoxicity prevents DKD•The beneficial effect is due to re-sensitizing podocytes to insulin signaling•Renal VEGF-B levels are increased in both experimental models and subjects with DKD•Reducing VEGF-B signaling may be a therapeutic strategy for the treatment of DKD Human studies have highlighted that hyperglycemia may not be the underlying cause of diabetic kidney disease (DKD). Falkevall et al. highlight a role for VEGF-B in renal lipotoxicity in mouse models and patients, offering a potential novel therapeutic approach to DKD.